Teaching jane austen - Narváez, Andrea; Pintado, Claudia
Learning literature can sometimes be difficult for students, especially if literature is used to teach a foreign language. When learning a foreign language, we have seen that memorization is one of the most important strategies used in the classroom. Although it is an important strategy, it is not the only one. For this reason, our work analyzes the use of role play when teaching literature, specifically the literary work Pride and Prejudice by Jane Austen. We believe this work will help instructors to teach this subject in a different way. This study aims to describe Jane Austen?s life, the social context she lived in, and her literary work Pride and Prejudice. Furthermore, this work makes an account of the importance of role play and offers a script of this novel as well as some role play activities which can be used by teachers to motivate students to learn about it in an interesting way.